Identification of TMCO2 as an acrosome‐associated protein during rat spermiogenesis. Issue 7 (27th June 2020) - Kaneko, Takane; Toh, Saori; Mochida, Izumi; Iwamori, Naoki; Inai, Tetsuichiro; Iida, Hiroshi
Abstract: We isolated the transmembrane and coiled‐coil domains 2 ( Tmco2 ) gene using a polymerase chain reaction‐based subtraction technique. Tmco2 is predominantly expressed in rat testes starting from 4 weeks of age. Rat TMCO2 consists of 187 amino acids with a predicted molecular mass of 20.6 kDa. When expressed in COS7 cells, TMCO2 was found as vesicle‐like structures in the cytoplasm, whereas TMCO2ΔTM lacking the transmembrane (TM) region was found diffused in the cytoplasm. These results suggest that the TM region in TMCO2 is essential for its specificity of localization. Immunocytochemical analyzes indicated that rat TMCO2 was localized as small semiluminate bodies or cap‐like structures in the vicinity of round spermatid nuclei and as curved lines associated with nuclei of elongated spermatids and caput epididymal spermatozoa. However, it was detected in only a small part of cauda epididymal spermatozoa. Double immunolabeling of the spermatids and spermatozoa with the anti‐TMCO2 antibody and the monoclonal anti‐MN7 antibody showed that TMCO2 was predominantly associated with the inner acrosomal membrane in spermatids and caput epididymal spermatozoa. Our findings suggest that TMCO2 might be involved in the process of acrosome biogenesis, especially binding of acrosome to a nucleus, during spermiogenesis. Abstract : Immunocytochemical analyzes indicate that rat TMCO2 was predominantly associated with the inner acrosomal membrane in spermatids and caput epididymal spermatozoa. In addition, the transmembrane region of TMCO2 is essential for its specificity of localization. Our findings suggest that TMCO2 might be involved in the process of acrosome biogenesis, especially binding of acrosome to a nucleus, during spermiogenesis.